Gender Differences in the Pro- and Antioxidant Systems of the Brain in the Late Postresuscitative Period (an experimental study) - A. G. Zhukova; T. G. Sazontova; Yu. V. Arkhipenko; A. V. Volkov (Общая реаниматология)
Objective: to study gender differences in the pro- and antioxidant systems of the brain in the late postresuscitative period after clinical death. Materials and methods. The brain tissue was studied for the resistance of membrane structures to free radical oxidation and the level of proteins with antioxidant activity in 40 adult albino rats of both sexes in the control and after experienced 12-minute cardiac arrest 4 months of the postresuscitative period. Results. There were gender differences in the level of protective proteins and in the resistance of brain membrane structures in the control and in the late postresuscitative periods. Furthermore, not only quantitative changes in the level of protective proteins, but also their spectrum alteration, were revealed in the postresuscitative period. Conclusion. Further investigations of gender-dependent mechanisms for the occurrence of postresuscitative diseases are needed to develop specific methods for its therapy and prevention. Key words: systemic circulatory arrest; cerebral cortex; free radical oxidation; the body’s protective systems: antioxidant defense enzymes, HSP70, heme oxygenase-1, peroxiredoxin.